2020
DOI: 10.3390/su12072844
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Improvement and Pollutant Removal by Two Regional Detention Facilities with Constructed Wetlands in South Texas

Abstract: Stormwater runoff introduces several pollutants to the receiving water bodies that may cause degradation of the water quality. Stormwater management systems such as detention facilities and wetland can improve the water quality by removing various pollutants associated with the runoff. The objective of this research project is to determine the performance and efficiency of two major regional detention facilities (RDFs) with different designs and structures in reducing pollutants based on various storm events i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…NBS such as constructed wetlands, restored floodplains, detention ponds, and barrier removals can improve freshwater quality through various mechanisms including sedimentation, denitrification, and anaerobic ammonium oxidation [75,76]. For instance, constructed wetlands remove pollutants and excess nutrients, such as nitrogen and phosphorus, from stormwater runoff by increasing residence time and providing conditions for the metabolism and settling [77,78]. These nutrients are absorbed by the soil and taken up by plants and microorganisms [79].…”
Section: Improve Water Qualitymentioning
confidence: 99%
“…NBS such as constructed wetlands, restored floodplains, detention ponds, and barrier removals can improve freshwater quality through various mechanisms including sedimentation, denitrification, and anaerobic ammonium oxidation [75,76]. For instance, constructed wetlands remove pollutants and excess nutrients, such as nitrogen and phosphorus, from stormwater runoff by increasing residence time and providing conditions for the metabolism and settling [77,78]. These nutrients are absorbed by the soil and taken up by plants and microorganisms [79].…”
Section: Improve Water Qualitymentioning
confidence: 99%
“…Méndez et al (2009) applied various stormwater quality improvement devices (SQIDs) including a SF CW system for the removal of fecal coliforms in stormwater, and observed that the fecal coliform concentration decreased by 20-98% under various rainfall event intensities (Méndez et al, 2009). A recent study evaluated the performance of two detention basins which were incorporated with CW for the removal of indictor bacteria (E. coli) from urban runoff, and the removal of E. coli was very low in one of the detention facilities (only 4% reduction), while in another basin, a high variation of E. coli removal was noticed (Guerrero et al, 2020). In an integrated constructed wetland system, the removal of total coliforms and E. coli from farmyard runoff was 99.2 and 99.9%, respectively (Mustafa et al, 2009).…”
Section: Removal Of Microbial Pollutantsmentioning
confidence: 99%
“…The effectiveness of SCMs in reducing nitrogen transport depends on the biochemical processes that are active within the sites. There are several potential removal mechanisms for nitrogen in SCMs including immobilization, adsorption, and denitrification [8,13,14]. Immobilization is the uptake of NH 4 + and/or nitrate (NO 3 − ) by plants and/or microorganisms resulting in a transformation of inorganic to organic nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…In some environments, denitrification rates may be limited based on the availability of carbon, which provides an energy (electron) source for microorganisms [8,20]. SCMs such as wetlands, which incorporate dense vegetation and have zones of stagnant water or water-logged soils, have the highest denitrification rate potential due to the build-up of soil organic matter and anaerobic conditions [14].…”
Section: Introductionmentioning
confidence: 99%